Pathological Proteins Are Transported by Extracellular Vesicles of Sporadic Amyotrophic Lateral Sclerosis Patients - Sproviero, Daisy; La Salvia, Sabrina; Giannini, Marta; Crippa, Valeria; Gagliardi, Stella; Bernuzzi, Stefano; Diamanti, Luca; Ceroni, Mauro; Pansarasa, Orietta; Poletti, Angelo; Cereda, Cristina (Frontiers in Neuroscience, 2018)
Amyotrophic Lateral Sclerosis (ALS) is a progressive adult-onset neurodegenerative disease, that affects cortical and spinal motor neurons, and it is considered a proteinopathy, in which misfolded proteins (SOD1, TDP-43 and FUS) may accumulate and interfere with neuronal functions eventually leading to cell death. These proteins can be released from cells and transported in the body fluids by extracellular vesicles (EVs). EVs are spherical vesicles, which are classified mainly in microvesicles (MVs) and exosomes (EXOs) based on their biogenesis, size and surface markers. In this study we characterized MVs and EXOs isolated from plasma of sporadic ALS patients and healthy controls and determined their number, size and misfolded protein composition. No variation was found in the number of EVs between ALS patients and controls. However, the mean size both for MVs and for EXOs resulted increased in ALS patients compared to controls. MVs derived from ALS patients were enriched in misfolded SOD1, TDP-43, phospho-TDP-43 and FUS proteins compared to CTRLs. Misfolded SOD1 was generally more concentrated in EXOs than in MVs, while TDP-43 and FUS protein levels were slightly higher in MVs than in EXOs. We demonstrated that MVs and EXOs size were increased in ALS patients compared to controls and that MVs of ALS patients were enriched with toxic proteins compared to CTRLs. EXOs did not show any protein changes. These data may suggest that MVs can transport toxic proteins and might play a role in prion-like propagation of ALS disease.